Clinical feature of omicron infection in children with inborn errors of immunity in China - Yang, Han; Sun, Fei; He, Ziwei; Li, Yan; Lu, Dan; Han, Tongxin; Mao, Huawei (Frontiers in Immunology, 2024)
Introduction SARS-CoV-2 infection is hypothesized to be more severe in immunocompromised patients; however, clinical outcomes in children with inborn errors of immunity (IEI) during the Omicron pandemic in China have not been reported. Methods This cohort study retrospectively reviewed 71 SARS-CoV-2-infected children with IEI using nationwide data from the National Center for Children’s Health of China. COVID-19 was diagnosed by a positive rapid antigen or nucleic acid test result. Results Among 71 SARS-CoV-2-infected children with IEI, male preponderance (male: female ratio of ~1.8:1), a median age of 8 years (IQR 3–11), and a predominance of antibody deficiency (19/71, 26.8%) were detected. Most of the patients got infected through household transmission, while a small proportion of them did so during hospital visits. The mean time periods were 3.3 days (n=44) for incubation, 8.4 days for symptoms (n=69), and 8.8 days for viral shedding (n=37). The time to viral shedding was proportional to the symptomatic period (R2 = 0.1243, p=0.0323) and prolonged in children with X- linked agammaglobulinemia. The most common symptoms of COVID-19 were fever, and some children showed only aggravation of the underlying disease. 15% of IEI children progress to pneumonia, 85% require medication, 17% are admitted to hospital, and 4.1% are classified as critical. Previously application of anti- infective medications was associated with an increased risk of hospitalization after COVID-19 infection. Of the 71 children with IEI, all recovered from COVID- 19. Conclusion Overall, Omicron variant did not cause significant life-threatening infections among children with IEI in China, and most of them had a good clinical outcome. Nevertheless, these children exhibit an increased vulnerability to higher hospitalization rates, pneumonia, and severe illness compared to the general pediatric population.